2019
DOI: 10.1142/s2424835519500383
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Radiographic Outcomes between 3D Preoperative Planning and Conventional Planning in the Osteosynthesis of Distal Radius Fractures

Abstract: Background: To assess the usefulness of three-dimensional (3D) digital pre-operative planning, we compared the radiographic parameters of the distal radius from 3D planning and conventional planning after osteosynthesis of distal radius fractures. We hypothesized that the use of 3D digital planning may improve radiographic outcomes for reduction and decrease the risk of correction loss.Methods: Sixty wrists of 60 distal radius fracture patients were randomly divided into two groups according to the order of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
0
19
0
6
Order By: Relevance
“…In our previous studies, we clinically applied the 3D preoperative planning system to the osteosynthesis of distal radius and humerus fractures [ 6 , 7 ]. It was found that 3D preoperative planning reduced postoperative correction loss and optimized implant selections [ 8 , 9 ]. The process of determining fracture reduction and placing the 3D models of the implants in virtual space aided decision makings during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we clinically applied the 3D preoperative planning system to the osteosynthesis of distal radius and humerus fractures [ 6 , 7 ]. It was found that 3D preoperative planning reduced postoperative correction loss and optimized implant selections [ 8 , 9 ]. The process of determining fracture reduction and placing the 3D models of the implants in virtual space aided decision makings during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…15 studies reported on reduction quality (Li et al, 2015(Li et al, , 2019Liu et al, 2017;Maini et al, 2018;Totoki et al, 2018;Chen et al, 2019;Hung et al, 2019;Yoshii et al, 2019b;Huang et al, 2020;Ramanathan et al, 2020;Wang et al, 2020a;Boudissa et al, 2021aBoudissa et al, , 2021bLong et al, 2021;Zheng et al, 2022), using different scoring systems, including the Matta scoring system (Matta and Tornetta, 1996), residual displacement (mm) and/or level of alignment compared to the healthy contralateral side. 12 studies reported on functional clinical scores (Li et al, 2015;Liu et al, 2017;Chen et al, 2018Chen et al, , 2019Chen et al, , 2020Huang et al, 2020;Jia et al, 2020;Ramanathan et al, 2020;Wang et al, 2020c;Long et al, 2021;He et al, 2022;Zheng et al, 2022) using scoring systems such as the VAS score, Harris score, Merle d'Aubigne score and range of motion (ROM).…”
Section: Reduction Quality and Functional Scoresmentioning
confidence: 99%
“…3. Choose optimal operative approach, e.g., appropriate choice of screw lengths and plate sizes (Yoshii et al, 2019b). 4.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY-NC-ND 4.0 (https://creativecommons.org/licenses/by-nc-nd/4.0/). preoperative 3D planning software in PS placement, although it has been applied in orthopedic procedures such as hip arthroplasty 16) , knee arthroplasty 17) , shoulder arthroplasty 18,19) , and surgeries of fractures 20,21) .…”
Section: Introductionmentioning
confidence: 99%